Messages from the past : rock art of Al-Hajar Mountains - Fossati, Angelo, 1958- (Archaeological heritage of Oman ;, 2019)
Angelo E. Fossati takes the reader on an in-depth journey into the various themes present in the rock art of Oman, offering theories on the chronology and interpretation, while exploring the landscape setting of the decorated. Highly illustrated throughout, beautiful photographs and scientific tracings of the rock art accompany the text.